2023
DOI: 10.31219/osf.io/gaum4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bridging Phenomenology and Neural Mechanisms of Inner Speech: ALE Meta-Analysis on Egocentricity and Intentionality in a Dual-Mechanistic Framework

Abstract: The neural mechanisms of inner speech remain unclear despite its importance in a variety of cognitive processes and its implication in aberrant perceptions such as auditory verbal hallucinations. Previous research has proposed a corollary discharge model in which inner speech is a truncated form of overt speech, relying on speech production-related regions (e.g. left inferior frontal gyrus). This model does not fully capture the diverse phenomenology of inner speech and recent research suggesting alternative p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
1
0
0
Order By: Relevance
“…4 By contrasting inner speaking and inner hearing of non-speech sounds, Chu et al (2023) recently showed a clear dissociation in the involvement of the motor-based and memory-based networks, further supporting the distinction between these two processes. Overall, our results are also compatible with the framework recently provided by Pratts et al (2023), in which inner speech can be generated by two separate mechanisms similar to those postulated by the dual stream prediction model, according to the intentionality and egocentricity constraints of the task.…”
Section: Discussionsupporting
confidence: 91%
“…4 By contrasting inner speaking and inner hearing of non-speech sounds, Chu et al (2023) recently showed a clear dissociation in the involvement of the motor-based and memory-based networks, further supporting the distinction between these two processes. Overall, our results are also compatible with the framework recently provided by Pratts et al (2023), in which inner speech can be generated by two separate mechanisms similar to those postulated by the dual stream prediction model, according to the intentionality and egocentricity constraints of the task.…”
Section: Discussionsupporting
confidence: 91%